Association of Hypertension and its risk factor in Type II diabetes mellitus patients - Singh, Seema; Gupta, Nitin Ranjan; Raza, Syed Tahseen; Kapoor, Avadh; Singh, Pooja (Asian Journal of Medical Sciences, 2021)
Background: There are few reports in India about the correlation of hypertension, its risk factors and its relationship with type II diabetes. Several studies have shown that Type II diabetes in India is increasingly widespread. Aims and Objective: The main purpose of this research is to determine the association between hypertension and type II mellitus diabetes. Materials and Methods: The Department of Physiology, Era Medical College & Hospital, Lucknow and the Department of Internal Medicine, Hind Institute of Medical Sciences and Research, Sitapur, performed a cross-sectional study on 520 patients with type II diabetes. The structured questionnaire was prepared to collect history of hypertension, social and demographical parameters and diabetes duration. A trained staff has measured anthropometric data like height, weight and also took blood pressure by digital blood pressure monitor (CITIZEN-CH-432). Results: This study indicated a significant (p<0.001) relationship between BMI and hypertension in diabetes mellitus II patients. This study has also shown significant relationship between physical activity and hypertension in diabetes mellitus patients. The logistic regression study demonstrated that hypertension in diabetes mellitus patients has been positively associated with age (p<10-4) sensitivity level (p<10-3) and period of diabetes (p<10-2). Conclusion: Hypertension is a common issue among diabetic Indians. This research focused primarily on the association of hypertension and its related risk factors in patients with diabetes. The study showed that hypertension in diabetic patients is associated with age, physical activity, awareness level and BMI. More studies on larger sample sizes are needed to validate the current findings.